ANALYSIS OF CONCEPTS UNDERSTANDING AND CAUSES OF STUDENT’S MISCONCEPTIONS IN HARMONIC VIBRATION MATERIAL IN PASAMAN REGENCY - Karzah, Khofifah; Mufit, Fatni (Physics Learning and Education, 2024)
Students who learn physics often get into misconceptions, one of which relates to the subject of harmonic vibrations. The teacher must be aware of both misunderstandings and their causes in addition to misconceptions themself. By being aware of the misunderstandings that students have, teachers can enhance the learning process and the learning results for their students. This study aims to evaluate the profile of students' misconceptions and their underlying causes using the harmonic vibration matrix. A five-level multiple choice test with 20 questions is used to determine misconceptions and their causes. Descriptive study using a quantitative methodology is the method used. Students from Pasaman State Senior High School made up the study's population. Two schools in this study's sample had high and low categories in Pasaman Distric with a total student sample of 177. Purposive sampling is used in this study's sample process. Overall, SMAN Pasaman Regency results show that misconceptions can be classified as moderate, at 36.5%. Based on the analysis, 35.8% of misconceptions in SMA B and 36.5% in SMA A fell into the high category. With a percentage of 82.60%, students' individual opinions are the main source of misconceptions.